Diversity of Arbuscular Mycorrhizal Fungi in Shola Forests of Kodaikanal, Southern India: Life Sciences-Botany for Medicinal science - Kullaiyan Sathiyadash; Jaffer Ali Jabeen; Karthigai Selvi Ezhilarasi; Eswaran Pillai Uma (International Journal of Life Science and Pharma Research, 2022)
Arbuscular mycorrhizal fungi establish symbiotic association with more than 80% of land plants and influence plant community composition and distribution. The mycorrhizal status of plant species in various ecosystems have been reported but failed to assess community composition of AM fungi in shola forests, therefore present study carried out to fulfill this research gap. A total of Seven AM fungal species could be isolated from Tiger and Kookal shoal and identified based on spore morphology. There is no significant difference among distribution of AM fungal spores in various seasons among sites. In both the sholas AM fungal spore numbers were high during the wet (September) season and the variation among spore numbers in different seasons among sites were insignificant. Arbuscular mycorrhizal spore of Funneliformis geosporum was the most frequent species and Funneliformis mosseae was the less frequent species. The frequency among various sites in both the Sholas was insignificant. The AM fungal species richness was high in Tiger Shola (six spores), whereas in Kookal Shola showed less species richness. The diversity indices like Shanon - Weaver index (H') and Simpson index (D) were calculated in all the sites and showed variation among shoals in four sites. Arbuscular mycorrhizal fungal community composition in this ecosystem have been elucidated to certain extent and used for conservation of shola species.